At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine which equation results from isolating a radical term and squaring both sides for the equation \(\sqrt{c-2} - \sqrt{c} = 5\), follow these steps:
1. Start with the given equation:
[tex]\[ \sqrt{c-2} - \sqrt{c} = 5 \][/tex]
2. Isolate one of the radical terms:
[tex]\[ \sqrt{c-2} = 5 + \sqrt{c} \][/tex]
3. Square both sides of the equation to eliminate the square roots:
[tex]\[ (\sqrt{c-2})^2 = (5 + \sqrt{c})^2 \][/tex]
4. Rewrite the squared terms:
[tex]\[ c-2 = (5 + \sqrt{c})^2 \][/tex]
5. Expand the right side:
[tex]\[ c - 2 = 25 + 10 \sqrt{c} + c \][/tex]
With these steps, we obtain the resulting equation:
[tex]\[ c - 2 = 25 + 10 \sqrt{c} + c \][/tex]
The correct answer is:
[tex]\[ c - 2 = 25 + c + 10 \sqrt{c} \][/tex]
1. Start with the given equation:
[tex]\[ \sqrt{c-2} - \sqrt{c} = 5 \][/tex]
2. Isolate one of the radical terms:
[tex]\[ \sqrt{c-2} = 5 + \sqrt{c} \][/tex]
3. Square both sides of the equation to eliminate the square roots:
[tex]\[ (\sqrt{c-2})^2 = (5 + \sqrt{c})^2 \][/tex]
4. Rewrite the squared terms:
[tex]\[ c-2 = (5 + \sqrt{c})^2 \][/tex]
5. Expand the right side:
[tex]\[ c - 2 = 25 + 10 \sqrt{c} + c \][/tex]
With these steps, we obtain the resulting equation:
[tex]\[ c - 2 = 25 + 10 \sqrt{c} + c \][/tex]
The correct answer is:
[tex]\[ c - 2 = 25 + c + 10 \sqrt{c} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.